ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN GOOGLE SITES PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR - Kirana Haliza, Cindy; Mansur, Nabilah; Kamil, Nurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning on plane geometry in elementary schools has not been optimally implemented due to the dominance of textbooks and lecture-based methods, resulting in limited use of digital learning media. This study aims to analyze the initial needs for developing Google Sites-assisted interactive learning media for fourth-grade students at SDN 10 Talang Kelapa. A descriptive qualitative approach was employed using observation and interviews with one teacher and three students. Data were analyzed using the Miles and Huberman model. The findings reveal that students prefer visual and digital learning, while both teachers and students require interactive media that are engaging, accessible, and capable of visualizing abstract concepts. Therefore, the development of Google Sites-based interactive learning media is considered appropriate to support more effective and meaningful mathematics learning.